2014
DOI: 10.1016/j.njas.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Energy use and greenhouse gas emissions in organic and conventional farming systems in the Netherlands

Abstract: Organic agriculture is often considered to contribute to reducing energy use and greenhouse gas (GHG) emissions, also on a per unit product basis. For energy, this is supported by a large number of studies, but the body of evidence for GHGs is smaller. Dutch agriculture is characterized by relatively intensive land use in both organic and conventional farming, which may affect their performance in terms of energy use and GHG emissions. This paper presents results of a model study on energy use and GHG emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 27 publications
1
50
1
5
Order By: Relevance
“…Also, Küstermann and Hülsbergen [19] state that organic farming systems produce less N 2 O and CO 2 emissions generally due to lower inputs. A similar conclusion had been previously reached by Haas et al [20], as well as Bos et al [21]. Daxbeck et al [22] claim that the conventional farming system produces a higher emission load than the organic one.…”
Section: Discussionsupporting
confidence: 84%
“…Also, Küstermann and Hülsbergen [19] state that organic farming systems produce less N 2 O and CO 2 emissions generally due to lower inputs. A similar conclusion had been previously reached by Haas et al [20], as well as Bos et al [21]. Daxbeck et al [22] claim that the conventional farming system produces a higher emission load than the organic one.…”
Section: Discussionsupporting
confidence: 84%
“…Studies exploring the impact of organic agriculture on greenhouse gas emissions have shown mixed results [35,41,56]. When measured on a per area basis, organic systems may fare better than conventional systems, but when the yield gap in organic is taken into effect, the emissions may be higher per unit of output [39,48].…”
Section: Challenges In Organic Agriculturementioning
confidence: 99%
“…Experimentally testing the scenarios examined here would require the farm systems to be operated for several years to ensure the accuracy of the data created. Examples of where models were used to undertake similar exercises include DairyWise (Schils et al, 2007), which has been used to compare the energy use and greenhouse gas emissions in organic and conventional farming systems (Bos et al, 2014). Similarly, the DAFOSYM model (Rotz et al, 1989) has been used to determine the effect on annual net return of using automatic milking systems across farms of different sizes (Rotz et al, 2003) or to determine the effect of feeding strategy and protein supplements on the nitrogen loss and profitability on farm.…”
Section: Models and Modelingmentioning
confidence: 99%